A Targeted Review of Current Progress, Challenges and Future Perspective of g‐C3N4 based Hybrid Photocatalyst Toward Multidimensional Applications. Issue 1 (26th October 2022) - Hayat, Asif; Sohail, Muhammad; Anwar, Usama; Taha, T. A.; Qazi, H. I. A.; Amina,; Ajmal, Zeeshan; Al‐Sehemi, Abdullah G.; Algarni, Hamed; Al‐Ghamdi, Ahmed A.; Amin, Mohammed A.; Palamanit, Arkom; et al.
Abstract: The increasing demand for searching highly efficient and robust technologies in the context of sustainable energy production totally rely onto the cost‐effective energy efficient production technologies. Solar power technology in this regard will perceived to be extensively employed in a variety of ways in the future ahead, in terms of the combustion of petroleum‐based pollutants, CO2 reduction, heterogeneous photocatalysis, as well as the formation of unlimited and sustainable hydrogen gas production. Semiconductor‐based photocatalysis is regarded as potentially sustainable solution in this context. g‐C3 N4 is classified as non‐metallic semiconductor to overcome this energy demand and enviromental challenges, because of its superior electronic configuration, which has a median band energy of around 2.7 eV, strong photocatalytic stability, and higher light performance. The photocatalytic performance of g‐C3 N4 is perceived to be inadequate, owing to its small surface area along with high rate of charge recombination. However, various synthetic strategies were applied in order to incorporate g‐C3 N4 with different guest materials to increase photocatalytic performance. After these fabrication approaches, the photocatalytic activity was enhanced owing to generation of photoinduced electrons and holes, by improving light absorption ability, and boosting surface area, which provides more space for photocatalytic reaction. In this review, various metals, non‐metals, metals oxide, sulfides, and ferrites have been integrated with g‐C3 N4 to form mono, bimetallic, heterojunction, Z‐scheme, and S‐scheme‐based materials for boosting performance. Also, different varieties of g‐C3 N4 were utilized for different aspects of photocatalytic application i. e., water reduction, water oxidation, CO2 reduction, and photodegradation of dye pollutants, etc. As a consequence, we have assembled a summary of the latest g‐C3 N4 based materials, their uses in solar energy adaption, and proper management of the environment. This research will further well explain the detail of the mechanism of all these photocatalytic processes for the next steps, as well as the age number of new insights in order to overcome the current challenges. Abstract : Graphical Abstract regarding the use of g‐C3 N4 in environment remedy. Graphitic carbon nitride (g‐C3 N4 ) is a shining star material due to its suitable band gap, abundance and better stability. Recent improvements of g‐C3 N4 composite materials were glanced in a comprehensive way and summed up. The fabrication, evaluation, and modification of such materials were analyzed. Numerous g‐C3 N4 applications in prospective functionalities were outlined. A few conclusion observations and suggestions for future research were made.